On Criminalization of Evasion from Payment of Insurance Contributions - N. V. Akhtyrskaya (Сибирское юридическое обозрение, 2018)
In July 2017 Federal Law № 250-FZ amended the Criminal Code of the Russian Federation related to tax evasion, fees and insurance premiums. To clarify the content of these short stories, the author refers to the corresponding provisions of the legislation of the Russian Federation on taxes and fees, compulsory insurance, identifies the contradictions that exist between them and the criminal legislation. In this paper, the criteria for differentiation by the legislator of insurance premiums for tax and non-tax payments are considered. The purpose of this paper is to develop proposals and recommendations on improving criminal liability for tax crimes by assessing the effectiveness of the adopted changes, identifying the merits and demerits of new versions of “tax” articles. According to the results of the research, the author suggests using the term “tax payments” in tax crimes.